Morphometric, meristic, and growth patterns of Anabas testudineusin the swamp area in the Sawah Village, Kampar District, Riau Province. - Winda Lestari; Ridwan Manda Putra; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractAnabas testudineus is a typeof freshwater fish that living inswamp area.Information on biological, including morphometric, meristic, and growth patterns of the fish is rare. To understand the morphometrical andmeristicalcharacteristics, and growth patterns of the fish, a research had been conducted from April to May 2018. There were 100 fishes (62.54-133.08 mm TL and 10.66-95.45 gr BW). There were 26 morphological characteristics measured and 11 meristical characteristics counted. The meristical characteristics were as follows: D. XV-XVIII, 10-14 P.10-14, V.I, 1-5 A. VII-X). The number of scale in the pre-dorsal fin was 5-18, in the cheek was 5-7, around the body was 11-18, in the caudal peduncle was 24-30, above lateral line was 8-12 and under lateral line was 11-15. There were 4 morphometrical characteristic differences between male and female A. testudineus. In male fish, distance between eye and mouth, anal fin length and eye diameter are longer than those of the female, but female has wider body width than male. The length-weight relationship shown that the growth of male and female was allometric positive. Keywords:climbing perch, allometric, morphological characteristic, meristical characteristic